Secure information flow by self-composition - Barthe, Gilles (2011)
Information flow policies are confidentiality policies that control information leakage through program execution. A common way to enforce secure information flow is through information flow type systems. Although type systems are compositional and usually enjoy decidable type checking or inference, their extensibility is very poor: type systems need to be redefined and proved sound for each new variation of security policy and programming language for which secure information flow verification is desired. In contrast, program logics offer a general mechanism for enforcing a variety of safety policies, and for this reason are favoured in Proof Carrying Code, which is a promising security architecture for mobile code. However, the encoding of information flow policies in program logics is not straightforward because they refer to a relation between two program executions. The purpose of this paper is to investigate logical formulations of secure information flow based on the idea of self-composition, which reduces the problem of secure information flow of a program P to a safety property for a program derived from P by composing P with a renaming of itself. Self-composition enables the use of standard techniques for information flow policy verification, such as program logics and model checking, that are suitable in Proof Carrying Code infrastructures. We illustrate the applicability of self-composition in several settings, including different security policies such as non-interference and controlled forms of declassification, and programming languages including an imperative language with parallel composition, a non-deterministic language and, finally, a language with shared mutable data structures.